Are Nepal's water, sanitation and hygiene and menstrual hygiene policies and supporting documents inclusive of disability? A policy analysis - Jane Wilbur; Nathaniel Scherer; Islay Mactaggart; Govind Shrestha; Thérèse Mahon; Belen Torondel; Shaffa Hameed; Hannah Kuper (BMC, 2021)
Abstract Purpose This study assesses the inclusion of disability in Nepal's policy and guidance relevant to water, sanitation and hygiene (WASH), and menstrual hygiene management (MHM) in comparison to gender. We investigated both policy formulation and implementation, using the Kavrepalanchok district as a case study. Materials and methods We used the EquiFrame framework, adapted for disability and gender, and focusing on WASH and MHM. Ten Nepali policies and guidance documents were reviewed and scored for quality against the framework, which included 21 core concepts of human rights. We also interviewed key informants to consider the inclusion of disability in the implementation of MHM interventions. We applied stratified purpose sampling to 12 government officials and service providers working in Kathmandu and the Kavrepalanchock district; conducted in-depth interviews and analysed data thematically using Nvivo 11. Results Disability was inadequately covered within the policy documents, and MHM policy commitments for disability were almost non-existent. Participation of people with disabilities in policy development was limited; within Kavrepalanchok, policy commitments were not implemented as intended and disability service providers were unable to allocate government resources. Inadequate data on disability and MHM resulted in limited professional understanding of the issues, as service providers had no training. A narrow WASH infrastructure approach to improving MHM for people with disabilities was prioritised. MHM interventions were delivered in schools; these failed to reach children with disabilities who are often out of school. Finally, there were indications that some caregivers seek sterilisation for people with disabilities who are unable to manage menstruation independently. Conclusion Though the Constitution of Nepal enshrines gender equality and disability inclusion, there are consistent gaps in attention to disability and MHM in policies and practice. These omit and exclude people with disabilities from MHM interventions. Investment is required to generate evidence on the MHM barriers faced by people with disabilities, which would then be drawn on to develop training on these issues for professionals to improve understanding. Subsequently, policy makers could include more concepts of human rights against disability in relevant policies and service providers could implement policy commitments as intended.